Phenotypic variation and leaf fluctuating asymmetry in natural populations of Parrotia persica (Hamamelidaceae), an endemic species from the Hyrcanian forest (Iran) - Sattarian, Ali; Reza Akbarian, Mohammad; Zarafshar, Mehrdad; Bruschi, Piero; Fayyaz, Payam (Instituto de Ecología, A.C., 2011)
Phenotypic variation in four natural populations of Parrotia persica (Hamamelidaceae), a species considered a living fossil endemic to the Hyrcanian forest, was evaluated through leaf morphometric and multivariate analysis. Furthermore, plasticity and leaf fluctuating asymmetry (LFA) were studied. Our findings clearly displayed significant divergence among sites. The smallest lamina size, the highest plasticity, and the lowest LFA values were recorded in the eastern and more xeric sites (Ghorogh and Daland), thus it seems these sites endure a larger environmental stress. Although our findings showed that multivariate and leaf morphometric analyses are suitable instruments to detect levels of phenotypic variability among P. persica natural populations, further study of allozyme and DNA diversity is necessary.